Allogeneic stem cell transplantation improves survival in patients with acute myeloid leukemia characterized by a high allelic ratio of mutant FLT3-ITD - Ho, Anthony Dick; Schetelig, Johannes; Bochtler, Tilmann; Schaich, Markus; Schäfer-Eckart, Kerstin; Hänel, Mathias; Rösler, Wolf; Einsele, Hermann; Kaufmann, Martin; Serve, Hubert; Berdel, Wolfgang E.; Stelljes, Matthias; et al. (Biology of blood and marrow transplantation, 2016)
Allogeneic hematopoietic cell transplantation (alloHCT) as a postremission therapy in patients with FLT3-ITD-positive intermediate-risk acute myeloid leukemia (AML) remains controversial. FLT3-ITD mutations are heterogeneous with respect to allelic ratio, location, and length of the insertion, with a high mutant-to-wild-type ratio consistently associated with inferior prognosis. We retrospectively analyzed the role of alloHCT in first remission in relationship to the allelic ratio and presence or absence of nucleophosmin 1 mutations (NPM1) in the Study Alliance Leukemia AML2003 trial. FLT3-ITD mutations were detected in 209 patients and concomitant NPM1 mutations in 148 patients. Applying a predefined cutoff ratio of .8, AML was grouped into high- and low-ratio FLT3-ITD AML (HRFLT3-ITD and LRFLT3-ITD). Sixty-one patients (29%) were transplanted in first remission. Overall survival (OS) (HR, .3; 95% CI, .16 to .7; P = .004) and event-free survival (EFS) (HR, .4; 95% CI, .16 to .9; P = .02) were significantly increased in patients with HRFLT3-ITD AML who received alloHCT as consolidation treatment compared with patients who received consolidation chemotherapy. Patients with LRFLT3-ITD AML and wild-type NPM1 who received alloHCT in first remission had increased OS (HR, .3; 95% CI, .1 to .8; P = .02) and EFS (HR, .2; 95% CI, .1 to .8; P = .02), whereas alloHCT in first remission did not have a significant impact on OS and EFS in patients with LRFLT3-ITD AML and concomitant NPM1 mutation. In conclusion, our results provide additional evidence that alloHCT in first remission improves EFS and OS in patients with HRFLT3-ITD AML and in patients with LRFLT3-ITD AML and wild-type NPM1.
Available online 10 November 2015
Gesehen am 14.05.2020